TIMP3 deficiency exacerbates iron overload-mediated cardiomyopathy and liver disease - Zhabyeyev, Pavel (Am J Physiol Heart Circ Physiol, 2018)
Chronic iron overload results in heart and liver diseases and is a common cause of morbidity and mortality in patients with genetic hemochromatosis and secondary iron overload. We investigated the role of tissue inhibitor of metalloproteinase 3 (TIMP3) in iron overload-mediated tissue injury by subjecting male mice lacking Timp3 (Timp3(−/−)) and wild-type (WT) mice to 12 wk of chronic iron overload. Whereas WT mice with iron overload developed diastolic dysfunction, iron-overloaded Timp3(−/−) mice showed worsened cardiac dysfunction coupled with systolic dysfunction. In the heart, loss of Timp3 was associated with increased myocardial fibrosis, greater Timp1, matrix metalloproteinase (Mmp)2, and Mmp9 expression, increased active MMP-2 levels, and gelatinase activity. Iron overload in Timp3(−/−) mice showed twofold higher iron accumulation in the liver compared with WT mice because of constituently lower levels of ferroportin. Loss of Timp3 enhanced the hepatic inflammatory response to iron overload, leading to greater neutrophil and macrophage infiltration and increased hepatic fibrosis. Expression of inflammation-related MMPs (MMP-12 and MMP-13) and inflammatory cytokines (IL-1β and monocyte chemoattractant protein-1) was elevated to a greater extent in iron-overloaded Timp3(−/−) livers. Gelatin zymography demonstrated equivalent increases in MMP-2 and MMP-9 levels in WT and Timp3(−/−) iron-overloaded livers. Loss of Timp3 enhanced the susceptibility to iron overload-mediated heart and liver injury, suggesting that Timp3 is a key protective molecule against iron-mediated pathology. NEW & NOTEWORTHY In mice, loss of tissue inhibitor of metalloproteinase 3 (Timp3) was associated with systolic and diastolic dysfunctions, twofold higher hepatic iron accumulation (attributable to constituently lower levels of ferroportin), and increased hepatic inflammation. Loss of Timp3 enhanced the susceptibility to iron overload-mediated injury, suggesting that Timp3 plays a key protective role against iron-mediated pathology.